The effect of institutional factors on the organizational performance through performance measures of commercial banks in Libya - Elnihewi, Ismail; Fadzil, Faudziah Hanim; Mohamed, Rapiah (Elsevier Ltd., 2014)
This paper aims to contribute to the literature that investigates the mediating role of performance measures in the link between institutional factors (coercive and normative pressure) and organizational performance.Using the data collected from 154 commercial bank branches in Libya, the results revealed the existence of a significant and positive association between coercive pressures and organizational performance through non-financial performance measures.However, the study found no evidence of a significant relationship between normative pressures and organizational performance through non-financial performance measures.